Estetika Sufistik Al-Ghazali dalam Inspirasi Hamka dalam Karya "Di Bawah Lindungan Ka'bah; & "Tenggelamnya Kapal Van Der Wijck" - Nuraini A. Manan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Patriotism in HAMKA concept cannot be separated from knowing God as another  manifestation of the love of God which is the highest love that exists in the universe, including  the love that also exists between the opposite sex. According to HAMKA, this love must be  sacred and to be based on devotion to God. HAMKA raises love as a common theme that  characterizes Western romance in addition to other characteristics. Through the power of  imagination and creativity, knowledge, experience and insight of Islam of HAMKA, then the  romanticism becomes more Islamic (Sufism) as an indicator of his predicate as a philosopher,  artist and scholar. Therefore, HAMKA is also called an Indonesian Islamic poet who can be  positioned parallel and even more to that of Hamzah Fansuri, Iqbal, al-Manfaluthi or Goethe.  Based on the above definition of romance, it is expected the studied art of literature will  describe a comprehensive and continuous mystical dimension in all aspects of life required by  each individual throughout his life. Although his work Di Bawah Lindungan Ka'bah (DBLK)  and Tenggelamnya Kapal Van de Wijk (TKVdW) were published in 1940s, the reprint of these  works are still easily found in the present.